Vloga sil zaščite, reševanja in pomoči pri obvladovanju poplavne ogroženosti - Kramer Stajnko, Janja (Gradbeni vestnik, 2019)
Floods are natural phenomena, which cannot be prevented and are causing many fatalities, enormous economic losses as well as present environmental threats. Therefore, it is crucial to set up an efficient flood risk management policy, which would reduce the likelihood and the impact of floods. The necessary elements of flood risk management according to %integrative risk management cycle% are preparedness (prevention, preparation), response (intervention, recondition) and recovery (reconstruction). Comprehensive structural and non-structural flood protection measures can reduce flood risk, but cannot eliminate the potential risk of flooding; therefore, an efficient civil protection service is an indispensable element in the system of flood risk management.
Keywords: cikel celovitega upravljanja ogroženosti; flood risk management; gradbeni in negradbeni protipoplavni ukrepi; integrative risk management cycle; obvladovanje poplavne ogroženosti; protection, rescue and relief forces; sile za zaščito, reševanje in pomoč; structural and non-structural flood protection measures